ANALISIS PENGUATAN KARAKTER KEIMANAN, KETAKWAAN DAN AKHLAK MULIA DI KELAS 5 SD - Maria Desinta; Muhammad Asrori; Agung Hartoyo (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to review and provide efforts to prevent students' moral crises about strengthening character, faith, piety and noble character of 5th grade elementary school students. This research uses the Library Research method. In this study, researchers collect various literatures that are in accordance with the subject of study, read, record, search, and express them theoretically in a frame of mind related to the character, faith, piety, and noble character of students. The data obtained were analyzed to find out the similarities and differences both theoretically and in reality in the field. From the results of this study, it can be concluded that strengthening students' character can be done inside and outside learning through faith, piety and noble character by paying attention to religious nuances.